(untitled) (Islas, 2024)
Introduction: Studies on the Cuban Revolutionary Party have occupied an essential part of Cuban historiography, focusing on the struggles for independence. However, these studies have centered on analyzing its organization and functioning in the United States. Methods: The research was based on documentary analysis and cross-referencing information from primary sources found in the National Archives of Cuba with existing scientific literature on the topic. Results: The research reveals the process of organization and functioning of the clubs affiliated with the Cuban Revolutionary Party in Jamaica, achieving greater precision regarding their number, names, and types, as well as an insight into their patriotic activities and their connection with José Martí. Conclusions: The Jamaican clubs directed their actions towards fundraising, organizing expeditions, and the civic and ideological formation of their members. Additionally, they made a fair assessment of Martí’s revolutionary leadership.